16‐Channel Organic Electrochemical Transistor Array for In Vitro Conduction Mapping of Cardiac Action Potential. Issue 18 (11th July 2016) - Gu, Xi; Yao, Chunlei; Liu, Ying; Hsing, I‐Ming
Abstract : 16‐Channel organic electrochemical transistor arrays (OECTs) are developed for mapping the propagation and studying the characteristics of action potentials of primary cardiomyocytes. The physiological activities of a rat cardiomyocyte monolayer during a long‐term culturing is revealed by this biocompatible, low‐cost, and high transconductance organic electronic device. OECT has great potential to be used in cardiac and neuronal drug screening.